Pengaruh Lahan, Modal dan Tenaga Kerja terhadap Produksi Kelapa Sawit di Kabupaten Barito Kuala (Studi Kasus Di Kecamatan Barambai) - Tamjidillah, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
To know simultaneously and partial factors influencing oil palm productionis done by quantitative method research. The Source of data used in the study isprimary data analyzed by using multiple linear regression analysis techniques andsecondary data sourced from relevant agencies or agencies. To determine the numberof samples conducted using the census method (sample saturated), the overallrespondents taken amounted to 65 people. The results of this study indicate thatsimultaneously (jointly) that the factors of production or dependent variables areinfluenced significantly by land area factors. In contrast, the capital factor does notinfluence substantially and negatively affect production; labor factors have a positivebut not influential effect significant to palm oil production factor. Partially factor ofthe land area significantly and considerable influence on palm oil production. Thecapital and labor factors have no significant effect on palm oil production.